Moments of uncertainty in therapeutic practice : interpreting within the matrix of projective identification, countertransference, and enactment - Waska, Robert T. (Columbia University Press, 2011)
One of therapy's greatest challenges is the moment of transference, when a patient unconsciously transfers emotion or desire to a new and present object, in some cases the therapist. During the course of treatment, a patient's projections and the analyst's struggle to divert them can stress, distort, or contaminate the therapeutic relationship. It may lead to various forms of enactment, in which the therapist unconsciously colludes with the client in interpretation and treatment, or projective identification, in which the client imposes negative feelings and behaviors onto the therapist, further interfering with analysis and intervention. Drawing on decades of clinical case experience, Robert Waska leads practitioners through the steps of phantasy and transference mechanisms and their ability to increase, oppose, embrace, or neutralize analytic contact. Operating from a psychoanalytic perspective, he explains how to cope professionally with moments of transference and maintain an objective interpretive stance within the ongoing matrix of projective identification, countertransference, and enactment. Each chapter discusses a wide spectrum of cases and clinical situations, describing in detail the processes that invite a playing out of the patient's phantasies and the work required to reestablish balance. Refreshingly candid, Waska recognizes the imperfections of analysis yet reaffirms its potential for greater psychological integration and stability for the patient. He acknowledges the limits and frequent roadblocks of working with difficult patients, such as those who suffer from psychic retreat, paranoid phantasies, and depressive anxieties, yet he indicates an effective path for resetting the clinical moment and redirecting the course for treatment.